1985
DOI: 10.1017/s0003356100036394
|View full text |Cite
|
Sign up to set email alerts
|

The effect of environmental temperature during pregnancy on thermoregulation in the newborn lamb

Abstract: Twenty-four pregnant Scottish Blackface ewes were divided into three temperature-treatment groups 14 days before expected lambing: closely shorn and kept at 6°C (cold treatment, CD); in full fleece at 26°C (warm treatment, WM); and in full fleece at 6°C (controls, CL). Food allocation and intakes were similar for each group. Their lambs were tested for cold-induced summit metabolic rate capability (SMR) on the day of birth at a mean age of 12 h using water immersion to provide cooling. On the following day, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
0

Year Published

1986
1986
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 26 publications
1
15
0
Order By: Relevance
“…rate) and by noradrenaline injection (increased by 2-4 times resting rate). The size of the cold-induced elevation in metabolic rate was very similar to that (3-5 times basal rate) reported by Alexander and Williams (1968) in Merino lambs and by Stott and Slee (1985) using Scottish Blackfaces as in the present experiment. However, our noradrenaline-induced peak metabolism was proportionately 0-66 of the cold-induced peak metabolism compared with only 0-31 found by Alexander and Williams.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…rate) and by noradrenaline injection (increased by 2-4 times resting rate). The size of the cold-induced elevation in metabolic rate was very similar to that (3-5 times basal rate) reported by Alexander and Williams (1968) in Merino lambs and by Stott and Slee (1985) using Scottish Blackfaces as in the present experiment. However, our noradrenaline-induced peak metabolism was proportionately 0-66 of the cold-induced peak metabolism compared with only 0-31 found by Alexander and Williams.…”
Section: Discussionsupporting
confidence: 90%
“…Thus, administration of a standard dose of noradrenaline should induce a thermogenic response from which differences in BAT-dependent NST capability can be measured. An infusion technique was used by Stott and Slee (1985) to measure variations in neonatal NST induced by physiological treatments during pregnancy. However, Slee,69 Simpson and Wilson (1987) showed that subcutaneous injection was the best method for large-scale experiments.…”
mentioning
confidence: 99%
“…It is known that the rate of loss of UCP can be delayed by hand-rearing at a cool ambient temperature (Darby, Clarke, Lomax & Symonds, 1996), but the exact time course of postnatal changes in adipose tissue development or the extent to which they may be linked to changes in body temperature remains to be established. The loss of BAT characteristics reflects the decreased requirements for non-shivering thermogenesis as a result of enhanced insulation via wool growth (Stott & Slee, 1985) and increased adipose tissue deposition (Darby et al 1996) in conjunction with improved thermal efficiency (Symonds, Bryant, Clarke, Darby & Lomax, 1992). This also coincides with the age at which plasma insulin-like growth-factor-I (IGF-1) concentrations increase rapidly depending on the level of food intake , although it has yet to be determined if this could be related to altered adipose tissue deposition as has been suggested in pigs (Brameld, Atkinson, Saunders, Pell, Buttery & Gilmour, 1996a).…”
Section: Introductionmentioning
confidence: 99%
“…Improved ewe nutrition in late pregnancy can reduce perinatal lamb mortality (Khalaf, Doxey, Baxter, Black, Fitzsimons and Ferguson, 1979a and b). Cold exposure of the ewe during pregnancy may also improve the subsequent cold resistance of the newborn lamb (Stott and Slee, 1985). These methods may however be impractical or uneconomic for the sheep farmer.…”
Section: Introductionmentioning
confidence: 99%